Krüppel-like factor 14 deletion in myeloid cells accelerates atherosclerotic lesion development. Issue 2 (4th February 2021) - Wang, Huilun; Guo, Yanhong; Lu, Haocheng; Luo, Yonghong; Hu, Wenting; Liang, Wenying; Garcia-Barrio, Minerva T; Chang, Lin; Schwendeman, Anna; Zhang, Jifeng; Chen, Y Eugene
Abstract: Aims: Atherosclerosis is the dominant pathologic basis of many cardiovascular diseases. Large genome-wide association studies have identified that single-nucleotide polymorphisms proximal to Krüppel-like factor 14 (KLF14), a member of the zinc finger family of transcription factors, are associated with higher cardiovascular risks. Macrophage dysfunction contributes to atherosclerosis development and has been recognized as a potential therapeutic target for treating many cardiovascular diseases. Herein, we address the biologic function of KLF14 in macrophages and its role during the development of atherosclerosis. Methods and results: KLF14 expression was markedly decreased in cholesterol loaded foam cells, and overexpression of KLF14 significantly increased cholesterol efflux and inhibited the inflammatory response in macrophages. We generated myeloid cell-selective Klf14 knockout ( Klf14 LysM ) mice in the ApoE -/- background for the atherosclerosis study. Klf14 LysM ApoE -/- and litter-mate control mice ( Klf14 fl/f l ApoE -/- ) were placed on the Western Diet for 12 weeks to induce atherosclerosis. Macrophage Klf14 deficiency resulted in increased atherosclerosis development without affecting the plasma lipid profiles. Klf14 -deficient peritoneal macrophages showed significantly reduced cholesterol efflux resulting in increased lipid accumulation and exacerbated inflammatory response. Mechanistically, KLF14 upregulates the expression of a key cholesterol efflux transporter, ABCA1 (ATP-binding cassette transporter A1), while it suppresses the expression of several critical components of the inflammatory cascade. In macrophages, activation of KLF14 by its activator, perhexiline, a drug clinically used to treat angina, significantly inhibited the inflammatory response and increased cholesterol efflux in a KLF14-dependent manner in macrophages without triggering hepatic lipogenesis. Conclusions: This study provides insights into the anti-atherosclerotic effects of myeloid KLF14 through promoting cholesterol efflux and suppressing the inflammatory response. Activation of KLF14 may represent a potential new therapeutic approach to prevent or treat atherosclerosis. Graphical Abstract: